IMPLEMENTASI KERJASAMA ANTARA INDONESIA DAN TURKI DI BIDANG INDUSTRI PERTAHANAN TAHUN 2010-2017 - Trisi Khairunnisa, - (2018)
This study examines the Implementation of cooperation between Indonesia and Turkey in the defense industry in 2010-2017. This cooperation began with the signing of the MoU in Ankara Turkey in 2010. This research uses Qualitative method approach by searching the data according to the research topic. The results showed that Indonesia's interest in cooperation in the field of defense industry with Turkey because currently Indonesia wants equipment and equipment alutsista modernize equipment alutsista this is because Indonesia is aware of the development of an increasingly dynamic threat so that to maintain the NKRI need modern equipment Alutsista. The advantages of this cooperation Turkish country is not only willing to provide Transfer of Thechnology, but the Turkish side also offers cooperation from the beginning of the process of design, upgrading engine technology to production together even the Turkish side also agreed and willing to do marketing sales of joint defense equipment that has been made by both countries, Turkey chose Indonesia as a partner to develop armaments as Indonesia and Turkey do have good cooperative relationships outside the defense industry cooperation. Turkey considers Indonesia as a country that has strategic location in the field of trade, has a majority of Muslim population and country that can be taken into account in Asia, this can be an advantage for Turkey